Reducing vasospasm of vein and arterial conduits used in coronary artery bypass surgery: are solutions the solution or is preserved perivascular fat the answer? - Dashwood, Michael R.; Celik, Zeynep; Topal, Gokce (Frontiers in Physiology, 2025)
The three main conduits used for myocardial revascularization in patients with coronary artery disease (CAD) are the internal thoracic artery (ITA), radial artery (RA) and saphenous vein (SV). In coronary artery bypass grafting (CABG) conduits may be harvested with perivascular adipose tissue (PVAT) intact (pedicled) or removed (skeletonized). Various studies have shown that the patency rate of these bypass grafts may be affected by the preservation or removal of PVAT. Vasospasm is often encountered at harvesting, a condition that has both immediate and long term effects on graft performance. During surgery a variety of antispastic solutions are routinely used on conduits that have anti-contractile and/or vasorelaxant actions. Spasm may be abolished or reduced when PVAT is left intact at harvesting and this is particularly the case for the SV. The protective properties of PVAT are multifactorial, ranging from its mechanical properties in supporting the graft after implantation to the beneficial effect of adipocyte-derived factors. This review aims to outline the possible mechanisms through which preserved PVAT could alleviate vasospasm and improve conduit performance in CABG. Moreover, since preservation of PVAT reduces spasm at and after surgery this review also considers whether antispastic solutions are needed if conduits are harvested with PVAT intact.